Partial oxidation of Raffinate II and other mixtures of n-Butane and n-Butenes to maleic anhydride in a fixed-bed reactor - Brandstädter, Willi Michael (KIT Scientific Publishing, 2008)
The utilisation of the C4 streams of steamcrackers by converting raffinate II to maleic anhydride was studied. The oxidation reactions were investigated in a laboratory-scale fixed-bed reactor to determine reaction kinetics. The effects of pore diffusional resistance were investigated and explained. A two-dimensional pseudo-homogeneous reactor model was used for the simulation of a production-scale fixed-bed reactor. A flow scheme of the reactor section including a recycle was proposed.